The Effect of Human Resource Quality and Work Facilities on Employee Performance with Motivation as an Intervening Variable among Employees of PT Sanidata Putri Medika - Rahmawati Khoirun Nisa; Mamik Indaryani; Sutono (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Employee performance remains a critical determinant of organizational sustainability, yet inconsistencies persist regarding how human resource quality and work facilities contribute to performance outcomes, particularly when mediated by motivation. This study aims to examine the direct and indirect effects of human resource quality and work facilities on employee performance, with motivation positioned as an intervening variable. A quantitative approach was employed using primary data collected through structured questionnaires distributed to 120 respondents selected through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) to simultaneously assess the relationships among variables. The findings indicate that human resource quality has a positive and significant effect on employee motivation, while work facilities do not significantly influence motivation. Furthermore, human resource quality shows a positive but insignificant direct effect on employee performance. In contrast, work facilities demonstrate a positive and significant direct effect on performance. Motivation also exerts a positive and significant effect on employee performance, confirming its mediating role in strengthening the relationship between human resource quality and performance. These results highlight the importance of enhancing employee competencies, strengthening motivational factors, and ensuring adequate work facilities to improve organizational performance.